2023
DOI: 10.2174/1574888x16666211206150934
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Platelet-Rich Fibrin Extract Treatment Promotes the Proliferation and Differentiation of Human Adipose-Derived Mesenchymal Stem Cells through Activation of Tryptophan Metabolism

Abstract: Background: Advanced platelet-rich fibrin extract (APRFE) contains a high concentration of various cytokines that are helpful for improving stem cells repair function. Objective: However, the underlying mechanism of APRFE improving stem cell repairing is not clear. Methods: We produced APRFE by centrifuging fresh peripheral blood samples and isolated and identified human adipose-derived mesenchymal stem cells (ADMSCs). The abundance of cytokines contained in APRFE was detected by the Enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Moreover, cytokines secreted by ADSCs and PDGF, VEGF, FGF-2, EGF, IGF and TGF-β in APRFE effectively promote neovascularization ( 28 ). Studies have shown that APRFE is beneficial for ADSCs to migrate to the injured area and the factors of TGF-β1, VEGF and PDGF-AB contained in APRFE play an important role in the adhesion, proliferation and differentiation of ADSCs via activating three pathways (tryptophan metabolism, mTOR signaling pathway, and adipocytokine signaling) ( 29 , 30 ). In addition, the three-dimensional APRF is an important structure for platelet concentrate to function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cytokines secreted by ADSCs and PDGF, VEGF, FGF-2, EGF, IGF and TGF-β in APRFE effectively promote neovascularization ( 28 ). Studies have shown that APRFE is beneficial for ADSCs to migrate to the injured area and the factors of TGF-β1, VEGF and PDGF-AB contained in APRFE play an important role in the adhesion, proliferation and differentiation of ADSCs via activating three pathways (tryptophan metabolism, mTOR signaling pathway, and adipocytokine signaling) ( 29 , 30 ). In addition, the three-dimensional APRF is an important structure for platelet concentrate to function.…”
Section: Discussionmentioning
confidence: 99%